2021
DOI: 10.3389/fmicb.2021.630121
|View full text |Cite
|
Sign up to set email alerts
|

The Human Cytomegalovirus UL116 Glycoprotein Is a Chaperone to Control gH-Based Complexes Levels on Virions

Abstract: Human cytomegalovirus (HCMV) relies in large part upon the viral membrane fusion glycoprotein B and two alternative gH/gL complexes, gH/gL/gO (Trimer) and gH/gL/UL128/UL130/UL131A (Pentamer) to enter into cells. The relative amounts of Trimer and Pentamer vary among HCMV strains and contribute to differences in cell tropism. Although the viral ER resident protein UL148 has been shown to interact with gH to facilitate gO incorporation, the mechanisms that favor the assembly and maturation of one complex over an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…UL47, UL49, UL76 and US22 proteins are known to be part of the tegument, UL77 is located in the capsid; UL105, UL122 and UL89 are found in the nucleus of the host cells [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In addition, UL4, UL22A and UL116, which were predicted to have one transmembrane domain, were discarded because the transmembrane domain corresponded to the sequence of signal peptide [ 42 , 43 , 44 ]. In addition, RL13TRL14 and US33 (TB40-E_UNC strain) or ORFL27C and ORFL49W.IORF1 (AD169-BAC20) proteins were only found in one of the CMV studied strains and were not considered for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…UL47, UL49, UL76 and US22 proteins are known to be part of the tegument, UL77 is located in the capsid; UL105, UL122 and UL89 are found in the nucleus of the host cells [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In addition, UL4, UL22A and UL116, which were predicted to have one transmembrane domain, were discarded because the transmembrane domain corresponded to the sequence of signal peptide [ 42 , 43 , 44 ]. In addition, RL13TRL14 and US33 (TB40-E_UNC strain) or ORFL27C and ORFL49W.IORF1 (AD169-BAC20) proteins were only found in one of the CMV studied strains and were not considered for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, Calo and colleagues have shown that the HCMV UL116 protein is a non-disulfide bound gH-associated factor alternative to gL and that the gH-UL116 complex is inserted into the viral envelope of mature virus particles [ 133 ]. To date, a specific receptor for this glycoprotein complex has not been identified [ 134 ], and it is still under debate whether UL116 is part of a new functional gH complex or rather acts as a chaperone that mainly regulates the availability of gH on the virion envelope [ 135 , 136 ]. Though not fully understood, UL116 conservation between herpesviruses and its features reminiscent of adhesion factors suggest an important role in the process of membrane recognition and fusion.…”
Section: Determinants and Mechanism Of Syncytium Formationmentioning
confidence: 99%
“…It seems likely that differences in other viral genes contribute to the phenotype of VR1814 GF . Candidates are, for instance, the variants of gH, a component of the core fusion machinery (55), and UL116, a chaperone promoting the incorporation of gH/gL complexes into virions (56, 57).…”
Section: Discussionmentioning
confidence: 99%